PREVALENSI PENDERITA KATARAK PADA DIABETES MELLITUS TIPE 2 DI RUMAH SAKIT UMUM MEURAXA BANDA ACEH TAHUN 2016 - Feriyani Feriyani; Syarifah Nora Andriaty (Jurnal Sains Riset, 2021)
Cataract is a condition when the eye lense, which is usually clear and transparent, becomes cloudy or blurry. This kind of abnormality is not a tumour, and nor is it a growth of tissue inside the eye, but rather a condition when the lense becomes foggy. If the lense's haziness keeps increasing, eyesight itself will also turn blurry and this could result in blindness. The disease can be found at every age and in both genders, male and female. 50% of the case is found on patients with the age of 65-74 years old, while 70% is found on patients of more than 75 years old. Cataract usually plagues both eyeballs, with the thickness of the haziness not always existing. The purpose of this research is to perceive the demographic data of the cataract patients with diabetes mellitus type 2 at the Meuraxa general hospital, Banda Aceh. This is an observational descriptive research with cross-sectional program, with observational approach or better known as a method of collecting all data at once and at a specified time. The result of the research shows that the number of cataract occurrences with diabetes mellitus type 2 occurs on 3 male patients (27,3%) and 8 female patients (72,7%). Meanwhile, seeing from the aspect of age, the acquired data shows that cataract infects 4 people from the age group of 48-50 years old (36,4%), followed by 4 more people from the age group of 54-60 years old (36,4%) and 3 people from the age group of 61-64 years old (27,3%). This research concludes that females with diabetes mellitus mostly suffer from cataract.Keywords: cataract,diabetes mellitus type 2